ADAMTS8 Expression is a Potential Prognostic Biomarker for Postoperative Metastasis in Lymph Node-Negative Early-Stage Invasive Breast Carcinoma Patients - Li Y; Yang X; Sun J; Zhao Y; Zhou Q; Hua B (Dove Medical Press, 2021)
Yao Li,1,* Xin Yang,1,* Jie Sun,2 Yangyang Zhao,3 Qi Zhou,3 Bin Hua1 1Breast Center, Department of Thyroid-Breast-Hernia Surgery, Department of General Surgery, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 2Graduate School of Peking Union Medical College, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 3The Key Laboratory of Geriatrics, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Bin HuaBreast Center, Department of Thyroid-breast-hernia Surgery, Department of General Surgery, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of ChinaTel +86-10-85136127Fax +86-10-65132969Email huabinbjh@126.comPurpose: Invasive breast carcinoma (BC) is the most common malignant breast tumor. Most lymph node-negative (LN−) early-stage BC patients usually have a good prognosis, but 7% of patients still develop metastasis after surgery. It is not yet clear how to screen candidates with poorer prognosis in LN− early-stage patients, so that they can receive intensive therapy. Hence, we expect to identify a prognostic biomarker to assess postoperative metastasis in LN− early-stage BC patients.Patients and Methods: Screening and verifying of candidate genes by gene expression profiling of LN− early-stage BC samples (n = 640) from 3 independent public datasets. Univariable and multivariable Cox regression analyses showed the relation between the candidate genes and postoperative metastasis. Distant metastasis-free survival (DMFS) analysis was performed to examine the prognostic significance. Quantitative real-time polymerase chain reaction (qRT-PCR) assays were performed to examine ADAMTS8 expression and prognostic association in our clinical samples (n = 25).Results: In the discovery cohort (TCGA and GSE20685 datasets), we found that ADAMTS8 tend to be low expression in LN− early-stage BC, and low ADAMTS8 expression was associated with postoperative metastasis and shortened DMFS. Moreover, the above finding was confirmed in the validation cohort (GSE6538 dataset). Lower ADAMTS8 expression was related to poorer prognostic clinical stage and PAM50 subtypes and shorter DMFS. Gene enrichment analysis indicated that ADAMTS8 may be correlated with BC metastasis. qRT-PCR assays of our clinical tumor sample showed that patients with low ADAMTS8 expression seem to be prone to developing metastasis and have a shorter DMFS time.Conclusion: Our research shows that low ADAMTS8 expression is associated with postoperative metastasis and shortened DMFS in LN− early-stage BC patients, which suggests that ADAMTS8 may be a potential prognostic marker for postoperative metastasis in LN− early-stage BC patients.Keywords: ADAMTS8, lymph node-negative early-stage invasive breast carcinoma, distant metastasis-free survival, biomarker